High pressure excursion in a radial design oxygenator - Svec Ashley; Eadie Tyler; D’Aloiso Brandon; Arlia Peter (The Journal of ExtraCorporeal Technology)
Oxygenator high-pressure (HPE) is a phenomenon that can occur during cardiopulmonary bypass (CPB) in which the oxygenator inlet pressure increases rapidly, thereby limiting flow. Most perfusionists globally do not use inlet oxygenator pressure monitoring and therefore HPE is not often recognized. HPE may occur for various reasons, and it is not fully understood. Patient factors that put a patient at a higher risk of HPE are increased body surface area, blood type, and hematocrit count. Patient size, blood flow, and pressure drops of the oxygenator incorporated into the circuit can also increase the probability of an HPE occurring. This case study overviews our experience when dealing with an interesting case of HPE and the most up-to-date knowledge on appropriate steps to mitigate the effects on the patient.